Land use induced changes of organic carbon storage in soils of China - Wu, Haibin; Guo, Zhengtang; Peng, Changhui (Global Change Biology, 2003)
Abstract Using the data compiled from China's second national soil survey and an improved method of soil carbon bulk density, we have estimated the changes of soil organic carbon due to land use, and compared the spatial distribution and storage of soil organic carbon (SOC) in cultivated soils and noncultivated soils in China. The results reveal that ∼ 57% of the cultivated soil subgroups ( ∼ 31% of the total soil surface) have experienced a significant carbon loss, ranging from 40% to 10% relative to their noncultivated counterparts. The most significant carbon loss is observed for the non‐irrigated soils (dry farmland) within a semiarid/semihumid belt from northeastern to southwestern China, with the maximum loss occurring in northeast China. On the contrary, SOC has increased in the paddy and irrigated soils in northwest China. No significant change is observed for forest soils in southern China, grassland and desert soils in northwest China, as well as irrigated soils in eastern China. The SOC storage and density under noncultivated conditions in China are estimated to ∼ 77.4 Pg (10 15 g) and ∼ 8.8 kg C m −2 , respectively, compared to a SOC storage of ∼ 70.3 Pg and an average SOC density of ∼ 8.0 kg C m −2 under the present‐day conditions. This suggests a loss of ∼ 7.1 Pg SOC and a decrease of ∼ 0.8 kg C m −2 SOC density due to increasing human activities, in which the loss in organic horizons has contributed to ∼ 77%. This total loss of SOC in China induced by land use represents ∼ 9.5% of the world's SOC decrease. This amount is equivalent to ∼ 3.5 ppmv of the atmospheric CO 2 increase. Since ∼ 78% of the currently cultivated soils in China have been degraded to a low/medium productivities and are responsible for most of the SOC loss, an improved land management, such as the development of irrigated and paddy land uses, would have a considerable potential in restoring the SOC storage. Assuming a restoration of ∼ 50% of the lost SOC during the next 20–50 years, the soils in China would absorb ∼ 3.5 Pg of carbon from the atmosphere.

Distribution and storage of soil organic carbon in China - Wu, Haibin; Guo, Zhengtang; Peng, Changhui (Global Biogeochemical Cycles, 2003)
Surface soils hold the largest terrestrial organic carbon pool, although estimates of the world's soil organic carbon storage remain controversial, largely due to spatial data gaps or insufficient data density. In this study, spatial distribution and storage of soil organic carbon in China are estimated using the published data from 34,411 soil profiles investigated during China's second national soil survey. Results show that organic carbon density in soils varies from 0.73 to 70.79 kg C/m 2 with the majority ranging between 4.00 and 11.00 kg C/m 2 . Carbon density decreases from east to west. A general southward increase is obvious for western China, while carbon density decreases from north to south in eastern China. Highest values are observed in forest soils in northeast China and in subalpine soils in the southeastern part of the Tibetan Plateau. The average density of ∼8.01 kg C/m 2 in China is lower than the world's mean organic carbon density in soil (∼10.60 kg C/m 2 ), mainly due to the extended arid and semi‐arid regions. Total organic carbon storage in soils in China is estimated to be ∼70.31 Pg C, representing ∼4.7% of the world storage. Carbon storage in the surface organic horizons which is most sensitive to interactions with the atmosphere and environmental change is ∼32.54 Pg C.

Increasing net primary production in China from 1982 to 1999 - Fang, Jingyun; Piao, Shilong; Field, Christopher B.; Pan, Yude; Guo, Qinghua; Zhou, Liming; Peng, Changhui; Tao, Shu (Frontiers in Ecology and the Environment, 2003)